Interdisciplinaridade no projeto pedagógico do curso de Licenciatura Integrada em Educação em Ciências, Matemática e Linguagens - LIMA, Dioenio Paixão de (2020)
The present article seeks to investigate the evidence of interdisciplinarity in the Pedagogical Project of the Course of the year 2012 (PPC) of the Undergraduate Integrated Education in Science, Mathematics, and Languages, the Institute of Education in Math and Science, the Federal University of Pará. Chose the bibliographic research and documental analysis as a methodology using techniques of discourse analysis as it is a possible way to elucidate the implementation of the integration of curricular content, envisioned in this proposal unique is training of teachers of the Initial Years of Elementary Education and the Education of the Young and Adults (EJA),the search began for the source of course, by the brief grounds of interdisciplinarity, and its purpose over time getting to the Political Pedagogical Project of the course (PPC), all analyzed in a comprehensive way so that if you could get to the goal, was to find traces of the relationship interdisciplinary in the PPC,which consists of the Degree course, Integrated Education in Sciences,Mathematics and Languages, in the face of several facts and this article brought in its analysis evidences explicit that it is the creation of the course and within the PCC met several traces in which we can say along with the authors used in this article which confirm the presence of interdisciplinary.